The early recognition inventory ERIraos assesses the entire spectrum of symptoms through the course of an at-risk mental state - Maurer, Kurt; Zink, Mathias; Rausch, Franziska; Häfner, Heinz (Early intervention in psychiatry, 2018)
Aim Functional disability and social consequences frequently occur at the prodromal stage of schizophrenia. Efforts to recognize an increasing risk of psychosis onset have thus become a topical issue worldwide. This is to introduce the English version of the ERIraos early-recognition inventory. Methods The ERIraos, developed in a systematic, empirical approach from the Instrument for the Retrospective Assessment of the Onset of Schizophrenia, incorporates basic symptoms from the Cologne Early Recognition Study. The research version also includes as further predictive items so-called brief limited intermittent psychotic symptoms and attenuated psychotic symptoms from the Comprehensive Assessment of At-Risk Mental States instrument. Results The ERIraos with its 15-item screening Checklist and 50-item Symptom List permits early recognition of psychosis risk in three steps of decreasing sensitivity and increasing specificity. Step 1 relies on patients’ self-perception of symptoms, which prompt them to contact a primary health service. There, in Step 2, at-risk individuals are identified using the Checklist, characterized by a low-risk threshold, and referred to further examination using the Symptom List (Step 3). Information on symptom accumulation and increasing symptom severity enhances the instrument's predictive power. In a validation test, psychotic transitions increased linearly up to 50% over 2 years. Compared with other instruments and on the prodromal stage of depressive disorder, the ERIraos has shown good predictive capacity. Conclusions The ERIraos has been successfully employed as a two-step tool for the early recognition of psychosis risk in several German studies and translated into several foreign languages.
First published: 23 January 2016
Gesehen am 18.10.2019